2003
DOI: 10.1038/sj.bjc.6601248
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of metastases in axillary lymph nodes of breast cancer

Abstract: We have established a highly sensitive and quantitative reverse transcriptase -polymerase chain reaction (RT -PCR) method to detect axillary lymph node metastases of breast cancer. Amplifying cytokeratin 19 (CK19) mRNA transcripts using real-time TaqMan PCR made it possible to quantify axillary metastatic burden. Metastases in 358 axillary lymph nodes obtained from 23 breast cancers of 22 patients were investigated by conventional haematoxylin and eosin (H&E) staining, immunohistochemical staining and quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Because a possible cause of false-positive identification of lymph node metastases by RT-PCR assays might be the illegitimate expression of low levels of target mRNAs by non-neoplastic cells, real-time quantitative RT-PCR (qRT-PCR) assays have been developed to correctly identify lymph node metastases according to a threshold level of mRNA expression [15,20,29,36,48]. Very recently, dedicated kits and instruments for "rapid" quantitative RT-PCR assays have also become commercially available for the intraoperative detection of SLN metastases from breast carcinoma.…”
Section: Tumour Mrna Markersmentioning
confidence: 99%
“…Because a possible cause of false-positive identification of lymph node metastases by RT-PCR assays might be the illegitimate expression of low levels of target mRNAs by non-neoplastic cells, real-time quantitative RT-PCR (qRT-PCR) assays have been developed to correctly identify lymph node metastases according to a threshold level of mRNA expression [15,20,29,36,48]. Very recently, dedicated kits and instruments for "rapid" quantitative RT-PCR assays have also become commercially available for the intraoperative detection of SLN metastases from breast carcinoma.…”
Section: Tumour Mrna Markersmentioning
confidence: 99%
“…Secondly, intraoperative analysis of the sentinel node, via frozen sectioning, imprint cytology, immunohistochemistry (IHC) or more recently 'Genesearch' BLN (Biopsy Lymph node assay) real time RT-PCR assay, can provide an immediate diagnosis of the axilla and thus reduce the requirement for delayed axillary surgery [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using such markers in HNSCC have suggested a low specificity (Kawamata et al, 1999;Hamakawa et al, 2000a), particularly because of false-positive results associated with benign epithelial rests in lymph nodes found in 1.6% of cervical nodes, but only in lymph nodes from level I (Gnepp, 2000;Hamakawa et al, 2000b). The assay used in the present study, that is, RT -PCR detection of CK19 mRNA, has been developed in our laboratory for the detection of occult carcinomatous cells in mediastinal lymph nodes in non-small-cell lung carcinoma (Saintigny et al, 2005) and by other teams in various carcinomas (Van Trappen et al, 2001;Inokuchi et al, 2003;Favia et al, 2004). The primers and probe for CK19 mRNA detection were designed to avoid the detection of the two known pseudogenes (Rund et al, 1999;Van Trappen et al, 2001;Saintigny et al, 2005) and we used real-time RT -PCR with the Taqman chemistry.…”
Section: Discussionmentioning
confidence: 93%